A Biquadratic polynomial \text{A Biquadratic}^{\text{polynomial}}

Algebra Level 2

f ( x ) = p ( x ) ( x 1 ) + 1 f ( x ) = q ( x ) ( x 2 ) + 1 f ( x ) = r ( x ) ( x 3 ) + 1 f ( x ) = s ( x ) ( x 4 ) + 1 \begin{aligned} f(x) &= p(x)(x-1) + 1 \\f(x) &= q(x)(x-2) + 1 \\f(x) &= r(x)(x-3) + 1 \\f(x) &= s(x)(x-4) + 1 \end{aligned}

Let f ( x ) f(x) be a monic biquadratic polynomial, and p ( x ) , q ( x ) , r ( x ) , s ( x ) p(x),q(x),r(x), s(x) be monic cubic polynomials satisfying the system of equations above.

What is the value of f ( 5 ) f(5) ?


The answer is 25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

David Vreken
Jul 4, 2020

From the given equations, f ( x ) 1 = p ( x ) ( x 1 ) = q ( x ) ( x 2 ) = r ( x ) ( x 3 ) = s ( x ) ( x 4 ) f(x) - 1 = p(x)(x - 1) = q(x)(x - 2) = r(x)(x - 3) = s(x)(x - 4) , so four factors of f ( x ) 1 f(x) - 1 must include ( x 1 ) (x - 1) , ( x 2 ) (x - 2) , ( x 3 ) (x - 3) , and ( x 4 ) (x - 4) .

If f ( x ) f(x) is a monic biquadratic polynomial, then so is f ( x ) 1 f(x) - 1 , which means f ( x ) 1 f(x) - 1 can only have up to four factors, the ones given above.

Therefore, f ( x ) 1 = ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) f(x) - 1 = (x - 1)(x - 2)(x - 3)(x - 4) , which means f ( x ) = ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) + 1 f(x) = (x - 1)(x - 2)(x - 3)(x - 4) + 1 , and f ( 5 ) = ( 5 1 ) ( 5 2 ) ( 5 3 ) ( 5 4 ) + 1 = 25 f(5) = (5 - 1)(5 - 2)(5 - 3)(5 -4) + 1 = \boxed{25} .

Well written in a concise manner!

Mahdi Raza - 11 months, 1 week ago
Zakir Husain
Jul 4, 2020

A n a l y z i n g o n l y o n e p o l y n o m i a l \Large{Analyzing\space only\space one\space polynomial}

p ( x ) : p(x): f ( 2 ) = p ( 2 ) ( 2 1 ) + 1 = q ( 2 ) ( 2 2 ) + 1 f(2)=p(2)(2-1)+1=q(2)(2-2)+1 p ( 2 ) + 1 = 1 \Rightarrow p(2)\cancel{+1}=\cancel{1} p ( 2 ) = 0 . . . . . . . . . . [ A 1 ] \Rightarrow \boxed{p(2)=0}..........[A_1] f ( 3 ) = p ( 3 ) ( 3 1 ) + 1 = r ( 3 ) ( 3 3 ) + 1 f(3)=p(3)(3-1)+1=r(3)(3-3)+1 2 p ( 3 ) + 1 = 1 \Rightarrow 2p(3)\cancel{+1}=\cancel{1} p ( 3 ) = 0 . . . . . . . . . . [ B 1 ] \Rightarrow \boxed{p(3)=0}..........[B_1] f ( 4 ) = p ( 4 ) ( 4 1 ) + 1 = s ( 4 ) ( 4 4 ) + 1 f(4)=p(4)(4-1)+1=s(4)(4-4)+1 p ( 4 ) + 1 = 1 \Rightarrow p(4)\cancel{+1}=\cancel{1} p ( 4 ) = 0 . . . . . . . . . . [ C 1 ] \Rightarrow \boxed{p(4)=0}..........[C_1] From [ A 1 ] , [ B 1 ] [A_1],[B_1] and [ C 1 ] [C_1] and assuming that p ( x ) p(x) is a monic polynomial we get p ( x ) = ( x 2 ) ( x 3 ) ( x 4 ) p(x)=(x-2)(x-3)(x-4) f ( 5 ) = p ( 5 ) ( 5 1 ) + 1 = ( 5 2 ) ( 5 3 ) ( 5 4 ) ( 4 ) + 1 = ( 3 ) ( 2 ) ( 1 ) ( 4 ) + 1 = 25 \Rightarrow f(5)=p(5)(5-1)+1=(5-2)(5-3)(5-4)(4)+1=(3)(2)(1)(4)+1=25

A request to @Mahdi Raza to mention that p ( x ) , q ( x ) , r ( x ) , s ( x ) p(x),q(x),r(x),s(x) are monic polynomials.

Thanks for mentioning, done!

Mahdi Raza - 11 months, 1 week ago

What's a biquadratic polynomial? Is that just the same thing as a quartic (4th degree) polynomial?

Ved Pradhan - 11 months, 1 week ago

Log in to reply

@Ved Pradhan Yes

Mahdi Raza - 11 months, 1 week ago

f ( x ) = ( x 1 ) ( x 2 ) ( x 3 ) ( x 4 ) + 1 f(x)=(x-1)(x-2)(x-3)(x-4)+1

f ( 5 ) = ( 4 ) ( 3 ) ( 2 ) ( 1 ) + 1 = 25 \implies f(5)=(4)(3)(2)(1)+1=\boxed{25}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...